Differences in characteristics and interactions with close contacts among PWID in the San Diego Border Region before and during the COVID-19 pandemic - Lara K Marquez; Natasha K Martin; Steffanie A Strathdee; Britt Skaathun (Elsevier, 2024)
Background: Travel restrictions implemented to mitigate the spread of SARS-CoV-2 decreased mobility and reduced physical contact during 2020-2021 for many in the general population. This analysis explored changes to network contacts among people who inject drugs (PWID) in the San Diego Border Region (SDBR) by cross-border mobility before and during the COVID-19 era. Methods: Baseline data collected between October 2020-2021, from a cohort study of PWID in the SDBR were used to retrospectively describe differences in baseline characteristics across cross-border PWID groups (cross-border PWID [CB-PWID]: n = 206; San Diego PWID [SD-PWID]: n = 203; Tijuana PWID [TJ-PWID]: n = 202). Chi-square and Fisher's exact tests evaluated sociodemographic, injecting risk behaviors, harm reduction service history, incarceration history, non-fatal overdose, HCV, HIV. Median differences in sex, drug/alcohol, and close partners before and during the pandemic among all PWID and by cross-border PWID status were evaluated using Kruskal-Wallis tests. Pairwise associations across cross-border PWID groups were assessed using the Dwass, Steel, Critchlow-Fligner multiple comparison test. Results: Among 611 PWID, the number of sex, drug/alcohol-related partners and close contacts before and during the pandemic remained relatively stable (psex=0.71;pdrug/alcohol=0.15;pclose=0.09). PWID in San Diego experienced the greatest difference in drug/alcohol-related partners (median[IQR]:-1[-6,0]), while cross-border PWID reported the smallest change in close contacts versus pre-pandemic (median[IQR]:0[0,1]). PWID in Tijuana had the greatest proportion (87%) of close contacts who injected drugs of all three groups. Conclusions: Compared to pre-pandemic, the median number of sex partners, drug/alcohol-related partners, and close contacts remained stable among PWID in the SDBR. Future research should explore how these network contacts evolve over time.